Effect of DriconÂ® in Kenaf Core Particleboard Towards On Fire Performance - Saad, Mohamad Jani; Jalaludin, Zaihan; Kamal, Izran (Journal of Science and Technology, 2011)
One layer kenaf core particleboard was treated with one of the advanced fire retardants, Dricon® . The percentage of 8 % (w/w) and 12 % (w/w) of Dricon® were incorporated into three different board densities (350 kg/m3, 450 kg/m3 and 550 kg/m3) which were fabricated with three resin loadings (w/w) of urea formaldehyde (8%, 10% and 12%). Each of treated and untreated particleboard has been tested with blow torch and fire propagation tests. The fire propagation test was evaluated by using performance index (I), which indicates the level of heat release of the tested boards. Blow torch test resulted the decreasing of sample’s weight loss of the Dricon®’s sample than the control samples. Fire propagation test indicated lower value of performances index or lower heat release of the treated samples compared with the untreated ones.